Electrical properties of CIGS/Mo junctions as a function of MoSe2 orientation and Na doping - Yoon, Ju-Heon; Kim, Jun-Ho; Kim, Won Mok; Park, Jong-Keuk; Baik, Young-Joon; Seong, Tae-Yeon; Jeong, Jeung-hyun (WILEY, 2014)
The electrical properties of Cu(In,Ga)Se-2/Mo junctions were characterized with respect of MoSe2 orientation and Na doping level using an inverse transmission line method, in which the Cu(In,Ga)Se-2 (CIGS)/Mo contact resistance could be measured separately from the CIGS film sheet resistance. The MoSe2 orientation was controlled by varying the Mo surface density, with the c-axis parallel and normal orientations favored on Mo surfaces of lower and higher density, respectively. The effect of Na doping was compared by using samples with and without a SiOx film on sodalime glass. The conversion of the MoSe2 orientation from c-axis normal to parallel produced a twofold reduction in CIGS/Mo contact resistance. Measurements of the contact resistances as a function of temperature showed that the difference in CIGS/Mo contact resistance between the samples with different MoSe2 orientations was due to different barrier heights at the back contact. Comparison between Na-doped and Na-reduced samples revealed that the contact resistance for the Na-reduced system was four times of that of the doped sample, which showed more pronounced Schottky-junction behavior at lower temperature, indicating that Na doping effectively reduced the barrier height at the back contact. Copyright (c) 2013 John Wiley & Sons, Ltd.
Keywords: CU(IN,GA)SE-2 SOLAR-CELLS; MO BACK CONTACT; EFFICIENCY